Peran Pancasila dalam Pembentukan Undang-Undang Anti- Terorisme di Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Cintya Bella Marathusholia; Zahra Riyani Aulia; Melia Agustina Ramadhani (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This research discusses how Indonesia can integrate Pancasila values in anti-terrorism policies, amidst international pressure which often leads to harsher approaches based on the standards of Western countries. An approach that prioritizes security can conflict with Pancasila principles, such as respect for human rights and social justice. Pancasila as the basic ideology of the state emphasizes the importance of balance between individual rights and the interests of society. In facing the threat of terrorism, Indonesia needs to adopt policies that not only strictly enforce the law, but also prioritize prevention through education, community empowerment and strengthening human values. This research aims to analyze how Pancasila values are implemented in Indonesia's anti-terrorism policy and the challenges that arise in harmonization with international norms. Globalization and technological developments pose new challenges in the spread of radical ideology, so policies are needed that are responsive but still based on Pancasila. Indonesia's anti- terrorism legal policy must be able to balance tough law enforcement with a humanist and dialogical approach, in line with the spirit of Pancasila which upholds just and civilized humanity. It is hoped that this research can contribute to more humane and effective policies.